Redescription and neotype designation of Suphis fluviatilis Guignot, 1948 (Coleoptera: Dytiscoidea: Noteridae) and notes on other species of the genus - Urcola, Juan I.; Guimarães, Bruno A. C.; Torres, Patricia L. M.; Fery, Hans; Michat, Mariano C. (Zootaxa, 2023)
Suphis fluviatilis Guignot, 1948 was described based on a single female specimen, and according to the author, the type was deposited in the Museum National d’Histoire Naturelle (Paris, France). However, the diagnostic features of the specimen deposited under this name and provided with the respective labels deviate considerably from those given by Guignot in his original description. It is shown that this specimen belongs to Suphis notaticollis Zimmermann, 1921, confirming previous observations by Luis Grosso in 1980. Thus, a neotype of S. fluviatilis is designated to avoid instability of the nomenclature by the impending synonymy of S. fluviatilis with S. notaticollis. Suphis fluviatilis is redescribed in detail, including illustrations of the main diagnostic characters. The species is compared with other Neotropical Suphis species, in particular with S. notaticollis. Additionally, the male genitalia of Suphis intermedius Régimbart, 1903 are described for the first time, and a first record from Paraguay is given.